The use of integrative and complementary practices in leprosy-related pain is influenced by sociodemographic, clinical and care factors: A case-control study (Research, Society and Development, 2021)
Purpose: Study in order to evaluate the use of complementary and integrative practices for leprosy-related pain. Cross-sectional, descriptive and quantitative research carried out at the University Hospital and Medical Specialties Center of Sergipe between February and June 2019. Methods: 170 people with leprosy pain contributed socio-demographic data, resources used for pain relief and factors that hinder adherence to practices. For pain assessment, the Verbal Pain Scales, Descriptor Scales and the tester Douler Neuropathic 4 were used. Results: Neuropathic pain was present in 119 individuals (70.0%) and the pain was assessed as severe in 85 (50.0%). Half of them (86; 50.6%) reported using pain relief: restricted diet (50, 29.4%), exercise (32, 18.8%), massage (31, 18.2%), among others. The factors that most influenced adherence to practices: lack of information (65, 38.2%), economic reasons (36, 21.2%), subjective characteristics (34, 20.0%). Women (45, 60.0%, p = 0.0427), patients with the borderline clinical form of the patient (23, 74.2%, p = 0.0014), reporting a burning sensation on the skin (70, 55, 5%, p = 0.0437), and those monitored by a physiotherapist (11, 84.6%, p = 0.0178) showed greater adherence to the practices. Conclusion: It is concluded that several complementary and integrative practices are being used for pain relief, but sociodemographic, clinical and care factors can influence adherence to these interventions.